Sleep disorders of insomnia type in patients with amyotrophic lateral sclerosis - G. N. Levitskiy; M. G. Poluektov (Нервно-мышечные болезни)
Objective: to evaluate the rate of sleep disorders of insomnia type among patients with amyotrophic lateral sclerosis (ALS) and to study the connection between these disorders and clinical characteristics of the disease. Materials and methods. The study included 101 patients (50 men and 51 women) with confirmed ALS diagnosis; mean age was 58.9 ± 9.6 years. The patient data was evaluated using the ALS Functional Rating Scale Respiratory (ALSFRS-R), Hamilton Depression Rating Scale, and ALS-specific Quality of Life Scale. Results. Sleep disorders were observed in 77 (76.3 %) ALS patients, among whom slow progression was more common (χ2 criterion 3.2; р = 0.048), quality of life was significantly lower (t = –2.043; p = 0.044), and total score per the Hamilton Depression Rating Scale was significantly higher (t = –3.98; р = 0.0001). Patients were divided into 3 groups: The 1st group included patients with primarily motor disorders, the 2nd group included patients with pronounced emotional depressive disorders without severe motor disorders, and the 3rd group included patients with both factors but duration of the disease was longer than in the 2nd group. The rate of postsomniac disorders was significantly higher in the 2nd group than in the 1st group (p = 0.022), and combination of presomniac, intrasomniac, and postsomniac disorders was significantly higher in the 3rd group than in the 1st (р = 0.007). Conclusions. Sleep disorders associated with ALS are accompanied by various complaints (presomniac, intrasomniac, postsomniac, or their combinations) depending on the severity of motor or emotional disorders in these patients.